Risk and Solution of English Language E-Textbook for Non-English Study Program Students - Asti Gumartifa; Sri Yuliani; Sherly Marliasari (English Education Department, 2021)
Abstract: E-textbooks are also referred to as electronic books, printed downloads, or internet sources. A textbook is an ideal example of technology in active learning for university students. E-textbooks are becoming more great choice than paper textbooks. In several academic institutes at a campus like the University of Muhammadiyah Palembang, where every lecturer is allowed to have a personal laptop. Thus, it's critical to look into how e-textbooks are adopted and how they might alter students' learning processes. The purpose of this study is to see what the risks of learning are and how to optimize the solution for learning and using English e-textbook for non-English study program students. This research’s novelty provides solutions and even optimizations related to the existing advantages and disadvantages specifically faced by non-English department students in learning English through e-textbooks. The solutions and optimizations are discussed descriptively into the modern approach and innovative technology. Furthermore, this research is beneficial for students to learn English for specific purposes. Keywords: E-textbook, risk, helpful, technology, learning